The Artist and the Witness:: Jane Urquhart’s The Underpainter and The Stone Carvers - Gordon, Neta (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2003)
Jane Urquhart's The Underpainter takes a different approach than most Great War novels: it does not presume the implied authority of combatant's accounts, like Generals Die in Bed, but nor does it interrogate the war novel as a postmodern pastiche, as in Timothy Findley's The Wars. She presents a realistically conceived persona, while nevertheless questioning the authority of the unengaged artist to represent an historical event. Her extensive use of historical data is not applied in a postmodern method, but is rather inspiration for a fiction that refuses to grant itself full authority. Urquhart's The Stone Carversis similarly concerned with the paradoxical combination of control and detachment in the relationship between the artist and her work.